Outer Membrane Vesicles of Gram-Negative Bacteria: An Outlook on Biogenesis - Avila-Calderón, Eric Daniel; Ruiz-Palma, María del Socorro; Aguilera-Arreola, Ma. Guadalupe; Velázquez-Guadarrama, Norma; Ruiz, Enrico A.; Gomez-Lunar, Zulema; Witonsky, Sharon; Contreras-Rodríguez, Araceli (Frontiers in Microbiology, 2021)
Outer membrane vesicles (OMVs) from Gram-negative bacteria were first described more than 50 years ago. However, the molecular mechanisms involved in biogenesis began to be studied in only the last few decades. Presently, the biogenesis and molecular mechanisms for their release are not completely known. This review covers the most recent information on cellular components involved in OMV biogenesis, such as lipoproteins and outer membrane proteins, lipopolysaccharide, phospholipids, quorum-sensing molecules, and cellular appendages, such as flagella.